Leukemoid-Like Reaction in a Post-Coronary Artery Bypass Grafting Surgery Patient - Ahmad, Usman; Sheikh, Maheen; Ahmed Khan, Junaid; Alam Khan, Iqbal (Pakistan Armed Forces Medical Journal, 2026)
A leukemoid reaction in post-cardiac surgery is uncommon. Few cases in the literature have reported a leukemoid-like reaction; furthermore, there are only a handful in cardiac surgery. The diagnosis of leukemoid reactions can be problematic for physicians. Even though leukemoid reactions are benign, in severe cases, excessive white blood cells can lead to tissue damage. Additionally, fatal conditions like malignancies can present similarly. Therefore, it is necessary to perform broad laboratory investigations. We present a case of a patient who had significant postoperative hyperleukocytosis following coronary artery bypass grafting (CABG). Various investigations were performed to rule out any sinister cause, like post-operative infections and malignancy; however, they came out negative. Furthermore, she did not develop any signs or symptoms during her stay or after discharge, and she was diagnosed with a leukemoid-like reaction and progressed to a good outcome. This case highlights the importance of avoiding unnecessary investigations and treatment, especially in resource-limited settings.